2013
DOI: 10.1007/s00701-013-1895-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of variation in the catechol-O-methyltransferase gene on the clinical outcome after lumbar spine surgery for one-level symptomatic disc disease: a report on 176 cases

Abstract: BackgroundThis study was aimed at the evaluation of the relationship between genetic polymorphisms of catechol-O-methyltransferase (COMT) (rs4680:A > G—Val158Met, rs6269:A > G, rs4633:C > T, rs4818:C > G) and pain sensitivity after lumbar discectomy.MethodsAll patients had one-level symptomatic disc herniation from L3 to S1. The primary data recorded included visual analogue pain scales assessing back and leg pain, Oswestry Disability Questionnaire assessing quality of life and pain intensity, received/filled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 30 publications
1
25
1
2
Order By: Relevance
“…In particular, three genes have shown consistent associations with both experimental and clinical pain responses: the catechol-O-methyl transferase gene ( COMT ), the mu-opioid receptor gene ( OPRM1 ), and the GTP-cyclohydrolase gene ( GCH1 ) [115]. Regarding COMT , polymorphisms and haplotypes have been associated with laboratory pain sensitivity, and acute and chronic clinical pain [13,40], including long-term outcomes after back surgery [143]. Similarly, the A118G polymorphism of OPRM1 has been associated with experimental pain sensitivity and with clinical pain [53,71,123], including long-term outcomes of acute back pain [124].…”
Section: General Considerationsmentioning
confidence: 99%
“…In particular, three genes have shown consistent associations with both experimental and clinical pain responses: the catechol-O-methyl transferase gene ( COMT ), the mu-opioid receptor gene ( OPRM1 ), and the GTP-cyclohydrolase gene ( GCH1 ) [115]. Regarding COMT , polymorphisms and haplotypes have been associated with laboratory pain sensitivity, and acute and chronic clinical pain [13,40], including long-term outcomes after back surgery [143]. Similarly, the A118G polymorphism of OPRM1 has been associated with experimental pain sensitivity and with clinical pain [53,71,123], including long-term outcomes of acute back pain [124].…”
Section: General Considerationsmentioning
confidence: 99%
“…Andrade et al [38, 39] used >20% reduction in VAS while Rut et al [40] and Takeuchi et al [41] used >50% reduction in VAS between baseline and follow to define recovery. Specific description of change in pain state during the follow up period was reported in just two of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…In both men and women, carriers of COMT rs4680 2G alleles had more pain than carriers of two A alleles at 6 months after disc herniation. Conversely, Rut et al [40] reported that carriers of two COMT rs4680 G alleles may be associated with significant positive improvement in pain recovery one year after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…According to their results, GG homozygotes are decidedly more resistant to pain stimuli than AA [24,25].…”
Section: Discussionmentioning
confidence: 99%